Antioxidant Activity of Frozen and Freeze-Dried Drone Brood Homogenate Regarding the Stage of Larval Development - Ewelina Sidor; Michał Miłek; Monika Tomczyk; Małgorzata Dżugan (MDPI AG, 2021)
Drone brood is a little-known and poorly studied bee product used and valued in the treatment of many diseases, including male infertility and women's menopausal disorders. The aim of this study was to evaluate the antioxidant activity of drone brood depending on the stage of larval development and the method of preservation. Aqueous and ethanolic homogenate extracts of drone brood were assayed for antioxidant activity (with the DPPH, FRAP, and ABTS methods), polyphenol, and flavonoid content. The extracts' polyphenolic profiles were compared by the HPTLC method. Drone brood has been shown to be more active in the earlier stages of development (between days 7-11), with a decline in antioxidant activity in the later period (by the 14th day). The freeze-drying process did not cause significant changes in the antioxidant activity of brood preparations converted to dry mass. Based on the higher activity of the aqueous compared to 70% ethanolic extracts, it was shown that the dominant fraction of brood consisted of hydrophilic antioxidants. The results obtained with different methods were highly correlated, excluding those from the ABTS assay. The HPTLC method showed that the polyphenol fraction of drone brood homogenate consisted mainly of phenolic acids and flavonoids. It was shown that drone brood has valuable antioxidant properties that can be compared with royal jelly.